PROBLEMS OF PRAYER TIME AND QIBLA DIRECTION IN OUTER SPACE - Muhamad Adib Abdul Haq (Fakultas Syari'ah dan Hukum UIN Walisongo, 2022)
The sun's shadow and addressing the Qibla, measured by several available methods, can be used to determine the times of prayer for Muslims who are on Earth's surface. The question of how to identify the prayer times and the direction of the Qibla emerges when a Muslim is in space. The aim of this paper is to identify the Qibla direction and prayer times in outer space. This qualitative article is based on a literature study. According to some of the findings of the scholars' ijtihād, Muslim astronauts could fly to Cape Canaveral depending on where they last left the earth, or they could follow the Greenwich Time or the Mecca prayer timetable. There are four alternatives for Qibla direction according to A Guideline for Performing Prayer at the International Space Station (ISS): addressing the earth, facing the projection of the Kaaba in the sky, approaching the earth, or facing everywhere.